Examining the mathematics performance of the first semester 'galus' students in Malaysian higher level institution / Sharifah Norhuda Syed Wahid … [et al.] - Syed Wahid, Sharifah Norhuda; Abu, Zurah; Ramli, Nazirah; Md Tahir, Herniza (Universiti Teknologi MARA Cawangan Pahang, 2009)
In the process of reaching a fully developed country by the year 2020, science, mathematics and technology subjects have been a significant focus in the education system in Malaysia. However, the mathematics performance among students as early as in the primary school until the higher level institution is still an issue. Therefore, the general focus of this paper is to examine the relationship and differences between the mathematics performance of the first semester students in higher level institution and their mathematics performance at Sijil Pelajaran Malaysia (SPM) level. 122 students of the 'galus' category students from one of the public universities in Malaysia were selected. The finding shows that there is a very weak positive relationship between mathematics performance of the first semester students and their mathematics performance at SPM level. In addition, it is found that the performance of students is not affected by gender but there is a relationship within female students which their mathematics performance in SPM level is better than first semester result in university. Besides that, student from the Science and Technology field with additional mathematics at the SPM level perform better in their mathematics during the first semester. Thus, the finding of this study is hoped to provide useful information in improving the mathematics performance in higher level institution